2004
DOI: 10.1016/j.femsle.2004.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Galangin expresses bactericidal activity against multiple-resistant bacteria: MRSA,Enterococcusspp. andPseudomonas aeruginosa

Abstract: The antimicrobial activity of three propolis ethanol extracts (EEP) was examined for various Gram-negative and Gram-positive bacterial species, including multiple-resistant Staphylococcus aureus, Enterococcus spp. and Pseudomonas aeruginosa strains. EEP had a good bactericidal activity against Gram-positive species, and all multiple-resistant bacterial strains tested were sensitive to EEP. Minimal inhibitory concentrations (MICs) were lower in samples of higher flavonoid content (from 0.65 to 7.81 mg mL(-1)), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
42
3
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(55 citation statements)
references
References 16 publications
4
42
3
6
Order By: Relevance
“…Nevertheless, the activities of the extracts were higher than the isolated compounds, which evidence a synergetic activity among the compounds present in the extracts. These results disagree with those found by Darwish et al [20] and Pepeljnjak and Kosalec [23]. These authors reported higher activity of pinobanksin-3-acetate, pinocembrin and galangin than crude extracts.…”
Section: Discussioncontrasting
confidence: 88%
“…Nevertheless, the activities of the extracts were higher than the isolated compounds, which evidence a synergetic activity among the compounds present in the extracts. These results disagree with those found by Darwish et al [20] and Pepeljnjak and Kosalec [23]. These authors reported higher activity of pinobanksin-3-acetate, pinocembrin and galangin than crude extracts.…”
Section: Discussioncontrasting
confidence: 88%
“…Another study showed that Turkish propolis, in combination with mupirocin, signifi cantly reduced MRSA nasal carriage in animals (Onlen et al, 2007). Only one report used a bioassay-guided fractionation process to isolate an anti-MRSA fl avonoid, identifi ed as galangin, from Croatian propolis (Pepeljnjak and Kosalec, 2004). The present study is the fi rst to report the anti-MRSA activity of propolis originating from the Pacifi c region (i.e..'Pacifi c propolis' (Bankova et al, 2005b)).…”
Section: Discussionmentioning
confidence: 70%
“…Inhibitory activity against enterococcal species and strains of Pseudomonas aeruginosa has also been reported but at quite high concentrations, c. 240 and 170 lg ml )1 , respectively (Pepeljnjak and Kosalec 2004). The mechanism(s) of action underlying this antibacterial activity is not clear, but data is available to indicate that inhibition of topoisomerase enzymes (Cushnie and Lamb 2006) and cytoplasmic membrane perturbation (Cushnie and Lamb 2005b) are both possibilities.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…In addition to this work, time-kill studies with galangin have shown that MIC levels of the flavonol are capable of causing decreases of 1000-fold and more in colony counts of antibiotic-sensitive S. aureus NCTC 6571 and b-lactamase-producing S. aureus NCTC 11561 populations (Cushnie et al 2003). Recent MBC assays by Pepeljnjak and Kosalec also indicate that the flavonol reduces colony counts of S. aureus below minimum detectable levels (c. 100 CFU ml )1 ) when used at concentrations of one to two times the MIC (Pepeljnjak and Kosalec 2004). Viable count reductions of this magnitude (NCCLS 1999) at one to two times the MIC (Prescott et al 1999) would immediately appear to suggest that galangin activity is bactericidal.…”
Section: Methods and Resultsmentioning
confidence: 99%